3 . 0 . ) + ( A Z B ) -gt; ( 1 A – 13 ) gt; BS , proof by deduction 7 – ) This formula equivalent for 1 ( A `B ) gt; ( ( T ABB ) = B ) 2 7) Apply

3 . 0 . ) + ( A Z B ) -> ( 1 A – 13 ) > BS , proof by deduction7 – ) This formula equivalent for1 ( A `B ) > ( ( T ABB ) = B )2 7) Apply Deduction !`ASB + ( }A – B ) = B3 2) Apply Deduction and time?`ASB, TAIB + 5S= TAVG, AVB LB ( DeMorgan )"We need to prove EMAVB, AVB, 183 is inconsistent.7. AVB , AVB, 73BV B/ Idempotency`of`3 . 6 ) | ( ( A J B ) – A ) > A , proof by deduction1 – ) Apply Deduction .`( A ` B ) – A FA= ( TAVB ) SAY A= ( AMTB ) VA + A